Analisis Yuridis Hak dan Kewajiban Warga Negara dalam Perspektif Hukum - Budiywono, Eko (IAI Darussalam, 2025)
Citizens have a fundamental role in the life of the nation and state, where they become both the subject and object in the administration of the state. Therefore, the state has an obligation to guarantee the rights of citizens and ensure they fulfill their duties. This research aims to analyze the rights and obligations of citizens from a legal perspective. The research method used is juridical-normative, by collecting and analyzing secondary data sourced from primary, secondary, and tertiary legal materials. The research results show that the rights of Indonesian citizens have been guaranteed in the 1945 Constitution, including the right to personal data, the right to a good and healthy environment, and the right to receive health services. On the other hand, citizens also have an obligation to obey the law, pay taxes, and participate in national development efforts. This research concludes that the state has a responsibility to protect and fulfill the rights of its citizens, while also ensuring that citizens fulfill their obligations in order to create an orderly and prosperous life as a nation and state